Evaluation of interfacial shear stress between multi-walled carbon nanotubes and epoxy based on strain distribution measurement using Raman spectroscopy. (June 2016) - Yashiro, Shigeki; Sakaida, Yoshihisa; Shimamura, Yoshinobu; Inoue, Yoku
Abstract: This study investigated the stress recovery of aligned multi-walled carbon nanotubes (MWCNTs) embedded in epoxy using Raman spectroscopy, and evaluated interfacial shear stress between MWCNTs and epoxy using shear-lag analysis. To this end, ultralong aligned MWCNTs (3.8 mm long) were embedded in epoxy to obtain Raman spectra at multiple points along the MWCNTs. Downshift of the G′-band due to tensile strain was measured from the nanotube end to the center, and the strain distribution of embedded MWCNTs was evaluated successfully. Interfacial shear stress was then estimated by minimizing the error between the shear-lag analysis and measured strain distribution. The maximum interfacial shear stress between the embedded MWCNTs and epoxy was 10.3–24.1 MPa at the failure strain of aligned MWCNT-reinforced epoxy composites (0.46% strain). Furthermore, the interfacial shear stress between an individual MWCNT and epoxy was investigated.